Tiempos fundacionales : nación, identidades y prácticas discursivas en las letras latinoamericanas - Kottow, Andrea; Massmann, Stefanie (Providencia, Santiago de Chile : Universidad Andrés Bello : RiL editores, 2015)
The articles in this book reflect on the culture of nineteenth-century Latin America and examine the significance of literature.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed January 23, 2017)
Keywords: Chilean literature -- 19th century -- History and criticism; Latin American literature -- 19th century -- History and criticism; Nationalism in literature; Chile -- History -- 19th century; Chile -- Intellectual life -- 19th century; Latin America -- History -- 19th century; Latin America -- Intellectual life -- 19th century; Electronic books